NUTRIENT CYCLING UNDER ISOLATED EXOTIC TREE STANDS IN THE RAINFOREST ZONE OF SOUTH-SOUTH NIGERIA (2014)
Cycling of nutrient elements by exotic tree species is becoming increasingly important to the sustenance and productivity of rainforest environment. Apart from the provision of shade and fruits to rural farmers, the incorporation of these exotic tree stands into farmland helps to return nutrients to the soil. Despite the importance of exotic trees in the rainforest environment, information on nutrient cycling under individual tree stands in south-south Nigeria has not been adequately documented. In this study, the cycling of nutrients under isolated exotic stands of Terminalia cattapa, Mangifera indica and Persea gratissima in Orogun, Ughelli North Local Government Area, south-south Nigeria, was therefore investigated. Litterfall, rainwash (throughfall and stemflow) and soil samples were collected from 15 stands of each of the three exotic tree species as well as 15 control plots in the rainforest. Litterfall and rainwash were collected daily for a year. Litterfall was collected with 1m² litter traps, throughfall and incident rainfall with funnel-type collectors; and stemflow with ¾ mm hose wound round the tree trunks. Soil samples were collected from 0-15 cm and 15-30 cm depth using core sampler. Nitrogen, phosphorus and potassium content of samples of litter, rainwash and soil, as well as soil organic matter were analysed using standard techniques. Descriptive statistics and ANOVA were used to compare nutrients returned to soil by the isolated trees and the control via litterfall and rainwash; while soil nutrients were correlated with litterfall and rainwash. From the stands of T. cattapa, M. indica, P. gratissima and the control, litter productions were 83.0, 76.5, 60.2 and 77.3 g/m²/yr; annual throughfall volumes (%) were 89.2, 88.6, 91.0 and 84.2; while stemflow volumes (%) were 6.5, 6.2, 7.6 and 7.3 of the incident rainfall (4325mm). The nitrogen returned to the soil via litterfall was 5.7±1.4, 3.4±0.4, 2.4±0.1 and 9.1±1.7 kg/ha/yr respectively for T. cattapa, M. indica, P. gratissima and the control. The corresponding values of phosphorus returned in litterfall were 0.7±0.2, 0.5±0.1, 0.4±0.1 and 0.6±0.1 kg/ha/yr; while for potassium were 4.9±1.3, 2.6±0.2, 2.1±0.4 and 3.4±0.8 kg/ha/yr. The potassium returned via throughfall for the isolated trees and the control were 10.6±5.9, 9.5±5.9, 7.4±4.4 and 8.8±5.7 kg/ha/yr; while the corresponding values of potassium returned via stemflow were 0.7±0.6, 0.3±0.3, 0.4±0.3 and 0.7±0.6 kg/ha/yr respectively. Nitrogen, phosphorus and potassium returned to soil via litterfall, throughfall and stemflow varied significantly (p<0.01) amongst the isolated exotic trees and the control. Litterfall, throughfall and stemflow accounted for 54%, 40% and 6% of the total quantities of nutrients returned to soil respectively. Litter production and soil organic matter correlated positively under T. cattapa (r=0.8), M. indica (r=0.8), P. gratissima (r=0.8) and the control (r=0.9). Soil nitrogen, phosphorus and potassium correlated positively with litterfall (r?0.2), throughfall (r?0.1) and stemflow (r?0.5) respectively. Isolated exotic trees over time returned nutrients to the soil, thereby improving soil nutrient status and sustaining soil productivity in the rainforest environment.